2018
DOI: 10.1109/tvcg.2017.2745958
|View full text |Cite
|
Sign up to set email alerts
|

Active Reading of Visualizations

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Abstract-We investigate whether the notion of active reading for text might be usefully applied to visualizations. Through a qualitative study we explored whether people apply observable active reading techniques when reading paper-based node-link visualizations. Participants used a range of physical actions while reading, and from these we synthesized an initial set of active reading techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 64 publications
(89 reference statements)
1
14
0
Order By: Relevance
“…• Interface actions operate on other data interface components. Examples include: take notes that are not bound to data items (e.g., document observations/questions/hypotheses/reflections/goals [54]), manage knowledge [45], externalize thoughts [117], and organize, open, close, maximize, and layout/rearrange the interface [54].…”
Section: Classifying Actionsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Interface actions operate on other data interface components. Examples include: take notes that are not bound to data items (e.g., document observations/questions/hypotheses/reflections/goals [54]), manage knowledge [45], externalize thoughts [117], and organize, open, close, maximize, and layout/rearrange the interface [54].…”
Section: Classifying Actionsmentioning
confidence: 99%
“…Non-data actions stress the challenge of fostering collaboration [55,80] and reflection over past activities [39,50,84]. Input actions -perhaps the most overlooked actions [62] -stress the challenge of enriching interaction means for data input [4,26,62], ranging from correcting erroneous data [82] to adding metadata and data-aware annotations [39,54,117] to creating knowledge from scratch [59,111]. From a broader perspective, input actions are the actions that allow to refine and integrate human knowledge into the data interface [118].…”
Section: Research Opportunities and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research started to study active reading of visualizations. Walny et al [37] conducted a series of studies on active reading with both printed and digital visualizations. They demonstrated that active reading behaviors previously observed on textual documents (e.g., underlining, writing notes in margin) occurred when people interpreted visualizations, and that such behaviors transferred in the digital world.…”
Section: Externalization In Visualizationmentioning
confidence: 99%
“…ActiveInk is built around a zoomable infinite canvas, on which people can drop visualizations, documents, and images, which we collectively refer to as views, and rearrange them. The ability to lay out the workspace, reorganize and manipulate views was previously shown to be an important component of active reading of visualizations [37]. Freeform inking is provided anywhere on the canvas and on views alike.…”
Section: Unified Infinite Canvasmentioning
confidence: 99%